2016
DOI: 10.1093/nar/gkw1041
|View full text |Cite
|
Sign up to set email alerts
|

SUBA4: the interactive data analysis centre for Arabidopsis subcellular protein locations

Abstract: The SUBcellular location database for Arabidopsis proteins (SUBA4, http://suba.live) is a comprehensive collection of manually curated published data sets of large-scale subcellular proteomics, fluorescent protein visualization, protein-protein interaction (PPI) as well as subcellular targeting calls from 22 prediction programs. SUBA4 contains an additional 35 568 localizations totalling more than 60 000 experimental protein location claims as well as 37 new suborganellar localization categories. The experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
381
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 392 publications
(399 citation statements)
references
References 37 publications
15
381
0
3
Order By: Relevance
“…Proteome sizes were estimated previously by Hooper et al . (). Marker collections are detailed in Table S3.…”
Section: Resultsmentioning
confidence: 97%
“…Proteome sizes were estimated previously by Hooper et al . (). Marker collections are detailed in Table S3.…”
Section: Resultsmentioning
confidence: 97%
“…Close examination of other up‐regulated DEGs identified that nine of them (g22426.t2 , g23216 .t1, g28049.t1 , g3557.t1 , g850.t1 , g9424.t1 , g20853.t1 , g9939.t1 , and g16955.t1 ) encode proteins that are predicted to be targeted to plastids in T. subterraneum (TargetP) or are homologs of genes that encode plastid‐localized proteins in Arabidopsis ( SUBA4 ; Hooper, Castleden, Tanz, Aryamanesh, & Millar, ; logFC > 2, FDR < 0.05, Table S1). These include IMMUTANS (plastid alternative oxidase, g28049.t1 ), two enzymes in thiamine synthesis ( g3557.t1 , g9424.t1 ), an alkenal/one oxidoreductase ( g20853.t1 ), and a plastid ABC transporter ( g22426.t2 ) (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…To specifically assess the extent of how much SnRK1 anterograde signaling could affect plastidial and mitochondrial proteins, we focused on nuclear-encoded targets of those TFs with a known or clearly predicted localization in plastids or mitochondria according to SUBA 4.0 (http://suba.live; Hooper et al, 2017). This analysis uncovered a remarkable list of nuclearencoded organellar proteins with important functions in mitochondria and chloroplasts (Supplemental Table S1).…”
Section: Anterograde Signals To Organelles Via Phosphorylation Of Tramentioning
confidence: 99%